Krishna Myths in Indian films: The Transformation of Images - Raguram, S. (My University, 2007)
The myths of Hinduism are closely associated with all forms of arts in India. The myths of Hinduism influenced the cinema sector since its inception in India. These myths were the initial moving force and platform of Indian cinema from the beginning. The concepts originated from stories and sub-stories of myths of Hinduism such as Mahabaratham, Ramayanam and Kalidhas’s Sakunthala were influenced the Indian movies produced at the initial period. The myth of Krishna was very much applied in Indian cinema to a greater extent, not only in spiritual space but also in the social, political and economic spaces too. Apart from direct expressions of this myth, these myths create a greater degree of indirect impacts. This phenomenon takes the research related to the influence of these myths to another dimension. However, the researcher feels that studying actors, their roles created to reflect mythical characters directly as well as indirectly, story structure backgrounds will not only serve as unpacking of myth but also unpack the politics behind them.
Keywords: Myths; Indian Films; God Krishna; Visual Images